Obesity management: a narrative review of treatments focusing on metabolic surgery (Research, Society and Development, 2022)
Obesity is a pathology characterized as a chronic non-communicable disease that results from a positive energy balance promoting the accumulation of adipose tissue, and contributes to the development of numerous pathologies. Some individuals with obesity may have treatment based on metabolic surgery, when physical activity and diet therapy and/or pharmacological intervention are not satisfactory. This narrative review article aims to describe the management of obesity and its treatments with a focus on metabolic surgery. For its elaboration, articles, books and their chapters, and other materials were used. Metabolic surgical procedures and interventions using alternative techniques for weight loss are divided into reversible and irreversible procedure techniques, performed in the stomach and/or stomach and small intestine, which promote side effects and possible post-surgical complications. In cases of nutrient malabsorption, supplementation of some vitamins and minerals is necessary. It is concluded that metabolic surgeries are effective alternatives for weight loss and in the treatment of other comorbidities, however they can generate post-surgical implications and irreversible side effects, requiring the adoption of new eating habits.